Aspectos petrográficos dos carbonatos da Formação Riachuelo - Albiano, bacia de Sergipe - Camacho, Daniel Garcia de Figueiredo [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
The carbonatic rocks have great importance in petroleum geology, since most hydrocarbons reservoirs in the world are associated to this kind of rock. The new giant petroleum fields discovered in the Brazilian southeast Atlantic margin are directly connected to calcareous rocks, which are subjacent to the Aptian evaporite pack. This demand an increase in the number of geologists able to study such deposits. The Aptian carbonatic platform is completely exposed only in the Sergipe-Alagoas Basin. Therefore, it works as a natural laboratory to the study and understanding of this kind of rock. The Sergipe Basin is situated in the east Brazilian coast, and has its evolutional history is intimately related to the formation of the South Atlantic Ocean, through the break-up of the Gondwana supercontinent. The marine sequence of the Brazilian marginal basins is of Albian age and is marked by the development of carbonatic platforms. In doing so, this paper aims to analyze the Albian limestones from Riachuelo Formation of the Sergipe Basin. The project gave to the student the opportunity to increase his knowledge in carbonates, due to the laboratory and outdoor activities. The studied deposits, within a regional outline, were petrografically described, allowing interpretations about the evolution of the former South Atlantic Ocean. Ten points were visited where samples were collected for making of thin sheets. In this work several carbonatic facies were identified totaling 116 laminates described.

As rochas carbonáticas têm larga importância para a geologia do petróleo, uma vez que grande parte das reservas de hidrocarbonetos no mundo está associada a este tipo de rocha. Os novos campos gigantes de petróleo descobertos no Brasil, na margem atlântica do sudeste brasileiro, conectam-se diretamente a rochas calcárias subjacentes ao pacote salífero aptiano. Isto implica na necessidade de ampliar o quadro de geólogos capacitados no estudo de tais depósitos. A plataforma carbonática albiana é completamente exposta apenas na Bacia de Sergipe-Alagoas, sendo assim essa um ótimo laboratório para a iniciação, aprofundamento e entendimento deste tipo de rocha. A Bacia de Sergipe localiza-se no litoral leste brasileiro, e tem sua história evolutiva intimamente relacionada à abertura do Atlântico Sul, com a fragmentação do supercontinente Gondwana. A sequência marinha das bacias marginais brasileiras de idade albiana é marcada pelo desenvolvimento de plataformas carbonáticas. Assim, este trabalho visou analisar os calcários albianos da Formação Riachuelo da Bacia de Sergipe. O projeto propiciou ao estudante a oportunidade de uma iniciação em rochas carbonáticas, tema de grande importância para a geologia do petróleo, tendo incluído atividades de campo e de laboratório. Os depósitos, dentro de um arcabouço regional, foram caracterizados petrograficamente, permitindo interpretações da evolução do Oceano Atlântico Sul primitivo. Foram visitados 10 afloramentos onde foram coletadas amostras para confecção de lâminas delgadas. Ao todo foram descritas 116 lâminas neste trabalho onde foram identificadas diversas fácies carbonáticas.
Keywords: Petrologia; Rochas carbonaticas; Petrologia sedimentar; Carbonatic rocks; Sergipe basin